MIRERC 053/2025: Profiling of Lactic Acid Bacteria, Physicochemical and Nutritional Changes during Spontaneous Fermentation of Ameru Traditional Porridge - Caroline Kinya, Ntongondu; Dr. Cynthia N. Mugo; Dr. Joan Simam , (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Traditional fermented foods and beverages are often linked to indigenous communities and differ according to ethnicity, geography, substrates and fermentation type employed. Ameru traditional fermented porridge locally known as “Ucuru bwa gukia” by the Ameru community; is a cereal-based beverage produced through spontaneous fermentation. Lactic acid bacteria (LAB) are the predominant microorganisms present in traditional fermented products. Cereal-based fermented beverages are a rich source of nutrients, and probiotics and therefore, reported as health promoting foods. However, there is paucity in scientific documentation of LAB succession, physicochemical attributes, and nutrient changes across the fermentation process of Ameru traditional fermented porridge. This study aims to profile LAB, physicochemical, and nutrient composition changes at different time intervals of fermentation of Ameru traditional porridge. Culture-based microbiological techniques coupled with molecular techniques based on 16S rRNA sequencing will be employed for the identification and characterization of predominant LAB respectively, at different time intervals during fermentation of Ameru traditional porridge. Variations of pH, temperature, total soluble solids, and titratable acidity will be determined using standard procedures for each parameter. Proximate nutrient analysis of carbohydrate, fats, fiber, protein and ash contents will be determined using the Association of Official Analytical Chemists (AOAC, 2000) method. DNA extraction and PCR amplification for the 16S rRNA bacteria gene will be performed using universal primers 27F and 1492R. The amplified PCR products will be sent for sequencing. Quality assessments for sequences obtained will be done using FASTQC and sequence processing using QIIME2 and DADA2. Statistical analysis for 16S will be performed using phyloseq. Microbial counts of the porridge samples will be analyzed using (ANOVA) analysis of variance and (LSD) least significance variance using p≤0.05. Data will be compiled in Excel and statistical analysis will be carried out using SPSS.